Rios: território das águas às margens das cidades: o caso dos rios de Uruaçu-GO - Gercinair Silvério Gandara (Confins)
In this text I try to show that individuals produce their history, constructing their notions of nature and imprinting on it their mark. I have elected the rivers Maranhão, Passa Três and Ribeirão Machambombo in Uruaçu-GO as representative symbols of the Brazilian rivers that constitute a basic ingredient for city life to happen, but also become stages of environmental problems. As consequence, cities set aside by the rivers reverse and lead them to rivers at the edge of cities. Socio-environmental history presented itself as a possibility for analysis and reflection on the impressions inscribed in this process. However, other categories, conceptual and methodological concerns, were also presented as necessary to gather more consistent and fundamental contributions for this analysis.